Pengaruh Modal Fisik, Kemajuan Teknologi, dan Upah terhadap Produktivitas Tenaga Kerja di 10 Provinsi di Kawasan Timur Indonesia - Ekaria; Salma Nabila Asrizal (Jurnal Ketenagakerjaan, 2026)
Labor productivity is a crucial indicator for measuring a country’s economic performance, as it plays a significant role in enhancing competitiveness. The disparity in labor productivity between Western Indonesia (KBI) and Eastern Indonesia (KTI) has persisted over the past eight years, from 2016 to 2023. Among the seventeen provinces in KTI, ten provinces continue to face challenges related to low labor productivity. This persistent issue poses a major obstacle to achieving the Indonesia Emas 2045 Vision, which aims to improve public welfare, human capital quality, and sustained economic growth. Therefore, it is imperative to enhance labor productivity by examining the influence of human capital, physical capital, technological progress, and wages on labor productivity across ten provinces in KTI. The data employed in this study were obtained from the Statistics Indonesia (BPS) and the Ministry of Manpower. The findings reveal that labor productivity tends to stagnate. The share of the workforce with at least junior secondary education, the proportion of workers with internet access, and the Provincial Minimum Wage (UMP) exhibit an upward trend, whereas gross fixed capital formation (GFCF) per worker shows a declining trend. Furthermore, the application of the Fixed Effect Feasible Generalized Least Squares Seemingly Unrelated Regression (FGLS-SUR) model demonstrates that GFCF per worker, UMP, and internet penetration among workers exert a positive impact on labor productivity, with GFCF contributing the most substantial effect.